The Incidence of HLA Antigens in Leprosy - U. Youngchaiyud (2018)
Abstract. HLA antigens were studied in 36 patients, with leprosy, 20 cases of lepromatous and 16 cases of tuberculoid type. Eleven out of 36 (30.55%) had BW40 as compared to 9.33% of 150 controls. The frequency of BW40 in tuberculoid patients (31.25%) was not different from that in lepromatous cases (30%). © 1977 Blackwell Publishing Ltd